Question
upstudy study bank question image url

Evaluate \[ \sum_{k=1}^{21} 5 k-12 \] \( \sum_{n=1}^{21}(6 n+3) \)

Ask by Ayala Fowler. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The sums are 903 and 1,449. \[ \sum_{k=1}^{21} (5k -12) = 903 \] \[ \sum_{n=1}^{21} (6n+3) = 1449 \]

Solution

Let's evaluate the two sums step by step. ### 1. Evaluate \(\sum_{k=1}^{21} (5k - 12)\) This sum can be split into two separate sums: \[ \sum_{k=1}^{21} (5k - 12) = 5 \sum_{k=1}^{21} k - 12 \sum_{k=1}^{21} 1 \] - **Sum of the first 21 integers:** \[ \sum_{k=1}^{21} k = \frac{21 \times 22}{2} = 231 \] - **Sum of 21 ones:** \[ \sum_{k=1}^{21} 1 = 21 \] Now, plug these values back into the equation: \[ 5 \times 231 - 12 \times 21 = 1155 - 252 = 903 \] ### 2. Evaluate \(\sum_{n=1}^{21} (6n + 3)\) Similarly, split this sum: \[ \sum_{n=1}^{21} (6n + 3) = 6 \sum_{n=1}^{21} n + 3 \sum_{n=1}^{21} 1 \] - **Sum of the first 21 integers:** \[ \sum_{n=1}^{21} n = 231 \] - **Sum of 21 ones:** \[ \sum_{n=1}^{21} 1 = 21 \] Now, calculate the sum: \[ 6 \times 231 + 3 \times 21 = 1386 + 63 = 1449 \] ### **Final Answers:** \[ \sum_{k=1}^{21} (5k - 12) = 903 \] \[ \sum_{n=1}^{21} (6n + 3) = 1449 \] Answer: After simplifying, the sums equal 903 and 1,449 respectively. \[ \sum_{k=1}^{21} (5k -12) = 903 \] \[ \sum_{n=1}^{21} (6n+3) = 1449 \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Beyond the Answer

To evaluate the expression \( \sum_{k=1}^{21} (5k - 12) \): First, we can break the sum into two separate sums: \[ \sum_{k=1}^{21} (5k - 12) = \sum_{k=1}^{21} 5k - \sum_{k=1}^{21} 12 \] Calculating each part: 1. The first sum \( \sum_{k=1}^{21} 5k \) can be factored out: \[ \sum_{k=1}^{21} 5k = 5 \sum_{k=1}^{21} k = 5 \cdot \frac{21 \cdot 22}{2} = 5 \cdot 231 = 1155 \] 2. The second sum \( \sum_{k=1}^{21} 12 \) can be calculated as: \[ \sum_{k=1}^{21} 12 = 12 \cdot 21 = 252 \] Putting it all together: \[ \sum_{k=1}^{21} (5k - 12) = 1155 - 252 = 903 \] Next, we evaluate the second expression \( \sum_{n=1}^{21} (6n + 3) \): Similarly, we can split this sum as well: \[ \sum_{n=1}^{21} (6n + 3) = \sum_{n=1}^{21} 6n + \sum_{n=1}^{21} 3 \] Calculating each part: 1. The first sum \( \sum_{n=1}^{21} 6n \): \[ \sum_{n=1}^{21} 6n = 6 \sum_{n=1}^{21} n = 6 \cdot \frac{21 \cdot 22}{2} = 6 \cdot 231 = 1386 \] 2. The second sum \( \sum_{n=1}^{21} 3 \): \[ \sum_{n=1}^{21} 3 = 3 \cdot 21 = 63 \] Now, adding these together: \[ \sum_{n=1}^{21} (6n + 3) = 1386 + 63 = 1449 \] Thus, the final results are: \[ \sum_{k=1}^{21} (5k - 12) = 903 \] \[ \sum_{n=1}^{21} (6n + 3) = 1449 \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy